Development of an electronic circuit cooling system using elastocaloric effect: a FEM comparison among different configurations. (25th January 2023) - Cirillo, Luca; Greco, Adriana; Masselli, Claudia
Highlights: Project of a device based on elastocaloric effect for cooling electronic equipment. The device is made of elastocaloric wires crossed by air as heat transfer fluid. Two different configurations were investigated: bending and tension of the wires. A numerical model to investigate working parameters has been developed. The model is used to draw a guide map for efficiently design the device. Abstract: In recent years the scientific community has been committed to finding new eco-friendly solutions for refrigeration. Among the Not-In-Kind Refrigeration Technologies very promising are those based on solid-state refrigerants. Solid-state refrigeration technologies are based on the caloric effect. The nature of the applied field (magnetic, electric, mechanical) particularizes it in: magneto -, electro -, mechano - (elasto - or baro -) caloric effect. Among these, very interesting is the elastoCaloric Effect (eCE) -based one. The aim of the study introduced in this paper is to design and build an elastocaloric device specifically aimed at the cooling of the electronic circuits. At the best of our knowledge, there are not any other caloric solid-state systems specifically developed for this application in open literature. Furthermore, there are not any elastocaloric devices yet developed basing on bending as loading/unloading operation and at the same time thermodynamically exploiting the Active elastocaloric Regenerative refrigeration cycle. This paper reports a preliminary study where two different configurations are compared based on a two-dimensional numerical model. The substantial difference between the two configurations lies in the application of wires loading/unloading: tensile or bending. The device consists of 240 wires of Ni50.8 Ti49.2 alloy, for a total mass of 61 g, with a diameter of 0.5 mm and a length of 300 mm crossed by air as heat transfer fluid. In this paper a comparison between the energy performances of the two configurations has been carried out (in terms of temperature span, cooling power and COP): the results reveal that the device based on wires bending gives the best performances (+50 % as COP with bending rather than loading).